Schmerz als interdisziplinärer Forschungsgegenstand: Der Schmerzbegriff in Viktor von Weizsäckers medizinischer Anthropologie und seine Bedeutung in der ärztlichen Praxis - Henß, Peter Uwe (EUKLID : Europäische Kultur und Ideengeschichte. Studien, 2013)
This study considers pain as at once both a medical and cultural phenomenon. It takes as starting point the essays and lectures of Viktor von Weizsäcker, who undertook in his Medical Anthropology to highlight this phenomenon.The central objective of the present investigation is the contemporary significance which may be assigned to the historical conceptions of pain developed in Weizsäcker’s Medical Anthropology – against the background of current findings in physiological and biotechnical pain rearch. This throws open the question of the boundaries of the conceptions at the core of Medical Anthropology.